2020
DOI: 10.21203/rs.3.rs-25101/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence of Non-Communicable Diseases and its Risk Factors among Ijegun-Isheri Osun Residents in Lagos State, Nigeria: A Community Based Cross-Sectional Study

Abstract: Background: The rapid epidemiologic transition of diseases has adverse implications for low-and middle-income countries (LMICs) like Nigeria due to their limited healthcare, weaker health systems and the westernization of lifestyle. There is a need to evaluate the enormity or otherwise of non-communicable diseases (NCDs) burden in such low resource settings. We performed this survey to determine the prevalence of NCDs and its risk factors among the Ijegun- Isheri Osun community residents of Lagos, Nigeria.Meth… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…This review revealed that heavy metals concentrations in human body are increasing with age of individuals in Nigeria. As these toxic elements can typically induce organ damage and cancers, it remains to be demonstrated whether there is correlation between metals level in human body and increasing number of deaths from noncommunicable kidney/heart failure and cancers in Nigeria (Olanrewaju et al, 2020;Idris et al, 2020). In the meantime, the review underscores the need for relevant food and drug agencies to pay more attention to locally made medicines in the country, with a view to prohibiting the sales and distribution of heavy metals -laden concoctions.…”
Section: Concluding Notesmentioning
confidence: 99%
“…This review revealed that heavy metals concentrations in human body are increasing with age of individuals in Nigeria. As these toxic elements can typically induce organ damage and cancers, it remains to be demonstrated whether there is correlation between metals level in human body and increasing number of deaths from noncommunicable kidney/heart failure and cancers in Nigeria (Olanrewaju et al, 2020;Idris et al, 2020). In the meantime, the review underscores the need for relevant food and drug agencies to pay more attention to locally made medicines in the country, with a view to prohibiting the sales and distribution of heavy metals -laden concoctions.…”
Section: Concluding Notesmentioning
confidence: 99%